2018
DOI: 10.1016/j.ajme.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Group B streptococcal carriage, antimicrobial susceptibility, and virulence related genes among pregnant women in Alexandria, Egypt

Abstract: 2018) Group B streptococcal carriage, antimicrobial susceptibility, and virulence related genes among pregnant women in Alexandria, a b s t r a c t Background and aim: Group B Streptococcus (GBS) has emerged as a leading cause of illness and death among neonates. The study was conducted to estimate the prevalence of recto-vaginal carriage of GBS among pregnant women at 35-37 weeks, gestation, to describe GBS antimicrobial susceptibility profile and to investigate selected virulence genes by PCR. Subjects and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
6
4
0
Order By: Relevance
“…We reported better sensitivity of GBS for chloramphenicol and azithromycin at 96.6% and 89.2%, respectively. This result is concurring with other findings reported in Egypt [ 50 ] and similar studies in Ethiopia [ 52 , 53 ]. Vancomycin was also one of the commonly utilized drugs for patients who poorly responded for clindamycin and for the cases with a risk of high anaphylaxis.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…We reported better sensitivity of GBS for chloramphenicol and azithromycin at 96.6% and 89.2%, respectively. This result is concurring with other findings reported in Egypt [ 50 ] and similar studies in Ethiopia [ 52 , 53 ]. Vancomycin was also one of the commonly utilized drugs for patients who poorly responded for clindamycin and for the cases with a risk of high anaphylaxis.…”
Section: Resultssupporting
confidence: 94%
“…Clindamycin and erythromycin could also be considered for patients who are allergic to penicillin once AST is performed [ 5 ]. Our finding is comparable with the studies conducted in Switzerland (8.2%) [ 49 ], Iran, Tehran (14.6%) [ 26 ], Egypt (22.6%) [ 50 ], Kenya (30.4%) [ 51 ], and Ethiopia (17.6–26.8%) [ 48 , 52 ].…”
Section: Resultssupporting
confidence: 89%
“…Resistance to erythromycin was 21.3% and to clindamycin 12.8%. This was similar to the results declared by Sadeka et al10 in Egypt, where all isolates (100%) were susceptible to penicillin, ampicillin, ceftriaxone, cefotaxime, cefepime, vancomycin, and linezolid while 22.6%, and 15% of isolated GBS were resistant to erythromycin and clindamycin, respectively. In Ethiopia, all isolated GBS were sensitive to penicillin, ampicillin, vancomycin, and gentamicin.…”
Section: Discussionsupporting
confidence: 90%
“…The maternal carriage rate of GBS was (23.5%) is in agreement with results obtained by two other studies in Egypt; in Alexandria the rate was found to be 26.5%10 and in Ismalia 25.3% 5. Also, the international prevalence rate of GBS carriage was found to be 24%, 20.7%, 18.4% in Kuwait, Lebanon, and Saudi Arabia, respectively 1,11.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation